Nilai-Nilai Pendidikan Agama Hindu Dalam Teks Geguritan Karma Phala - Gusti Ayu Putu Ulan Prabandari; Heny Perbowosari; Ni Komang Sutriyanti (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study aims to describe the text structure of geguritan karma phala, the value of Hindu religious education contained in the geguritan karma phala, and how the relevance of the geguritan karma phala text with Hindu religious education. The results of the study found: (1) The structure of geguritan karma phala includes: characterization, incident, plot, message, theme, and background. This characterization in geguritan karma phala displays the main character is Sang Dharmaputra because of the intensity of his involvement in every event that is happening. The secondary character is Chess Pandawa and Diah Drupadi. ​​This character is described analytically and dramatically. Complementary figures, namely Duryodhana, Rsi Bhisma, Bhagawan Drona, Prabu Salya and figures of gods such as Sang Hyang Indra, Sang Hyang Dharma. The incident in geguritan karma phala begins with the destruction of Dwarawati's kingdom followed by the departure of Panca Pandawa and Diah Drupadi doing Tirthayatra. The next incident is to tell about the journey of the Chess Pandawa until finally their deaths one by one on the journey. The last incident was, the return of all the Pandavas to surge where they had previously lived in hell, reversed with the Kuravas, where previously lived in the end of heaven lived in hell forever. (2) The value of Hindu religious education contained in the geguritan karma phala is the value of tattwa education, the value of ethical education, and the value of aesthetic education. The value of tattwa concerning Panca Sradha and about the philosophy of Color Chess. The value of ethical education regarding the value of loyalty. Aesthetic values ​​regarding a form of Geguritan story contain noble educational values ​​so that it can be used as a guide in living life. (3) The relevance of geguritan karma phala with Hinduism education that the teachings of Hindu religion are mostly contained in the turmoil of karma phala that can be applied in Hinduism education. The teachings in geguritan karma phala that are relevant to be applied in Hindu religious education are the teachings of Panca Sradha in Geguritan Karma Phala, namely five beliefs or beliefs and catur warna.